Risk Factors Associated with Long COVID Among Hospitalized Adults in Several Hospitals in Palembang City, Indonesia - Hutapea, Hotma Martogi Lorensi; Sudaryo, Mondastri Korib; Parikesit, Arli Aditya; Miko Wahyono, Tri Yunis; Salim, Nelda Aprilia (Kesmas, 2025)
Long COVID is characterized by one or more symptoms experienced by individuals prior to a COVID-19 infection that last for ≥2 months, and its risk factors remain unclear. This study aimed to identify risk factors associated with long COVID among patients admitted between June 1, 2020, and October 31, 2023, at three referral COVID-19 hospitals in Palembang City, Indonesia. This cohort study included adults who were admitted for ≥5 days. The participant’s medical records were reviewed for admission and discharge dates, sociodemographic and clinical characteristics, and vaccination and therapy status. A standardized and validated instrument was used to assess fatigue during admission, and a structured questionnaire was used to evaluate long COVID. Cox regression was employed to determine factors associated with long COVID. Among 256 patients, long COVID was identified in 39.1%. Fatigue during admission, chronic kidney disease, thrombocytosis, and positive RT-PCR test at hospital discharge increased the risk of long COVID, whereas being fully vaccinated decreased its risk. This study identifies five risk factors for long COVID and determines that fatigue during admission is the strongest.